Odpowiedzi

Najlepsza Odpowiedź!
2010-02-01T22:22:25+01:00
A) 4x-(x+6)+4 dla x=1/3

4*⅓-(⅓+6)+4=1⅓-6⅓+4=-1

b) (x²+1)-(x²-2)+10 dla x=2,2
(2,2²+1)-(2,2²-2)+10=(4,84+1)-(4,84-2)+10=5,84-2,84+10=13

c) (a+4b)-(5+2a)-(3b-5) dla a=-0,1 i b=0,2
(-0,1+4*0,2)-(5+2*(-0,1))-(3*0,2-5)=(-0,1+0,8)-(5-0,2)-(0,6-5)=0,7-4,8+4,4=0,3

d) (-a²+2ab-1)+(a²-4ab+5) dla a=¼ i b=2
(-¼²+2*¼*2-1)+(¼²-4*¼*2+5)=1/16+(1/16-2+5)=1/16+3 1/16=3 2/16=3⅛
196 3 196
2010-02-01T22:27:44+01:00
A. 4*⅓-⅓-6+4
1⅓-⅓-6+4
1-6+4 = -1

b. 4.84+1-4.84+2+10 = 13

c.(-0.1+0.8)-5+0.2-0.6+5
0.7-5+0.2-0.6+5 = 0.3

d.(-¼)^2+2*¼*2-1=(¼)^2-4*¼*2+5
1/16+1-1+1/16-2+5 = 3i2/16 = 3⅛
86 2 86